2007
DOI: 10.1159/000101466
|View full text |Cite
|
Sign up to set email alerts
|

Is Transcranial Doppler for the Detection of Venous-to-Arterial Circulation Shunts Reproducible?

Abstract: Background: We investigated the reproducibility of contrast transcranial Doppler (TCD), a safe non-invasive test for investigation of venous-to-arterial circulation shunts (v-aCS), usually patent foramen ovale, in young stroke patients. We also investigated whether microbubble contrast was reproducible and whether the addition of blood to agitated saline contrast affected the number of microbubbles produced. Methods: TCD investigation for v-aCS was repeated in 42 patients using a standardised protocol (i) by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
(25 reference statements)
1
40
0
Order By: Relevance
“…TCD has been demonstrated to have high sensitivity and specificity for detection of rightto-left shunting when compared to contrast transesophageal echocardiography and is superior to transthoracic echocardiography. [15][16][17][18][19][20][21][22] Transthoracic echocardiography (TTE) with agitated saline has decreased sensitivity of detecting an intracardiac shunt in OSA patients with elevated BMI and large body habitus secondary to limited acoustic windows. 13,21 Using passage of a guide wire across the atrial septum during cardiac catheterization with intracardiac echocardiography guidance as the standard for diagnosing a PFO, TCD has a 98% sensitivity for making the diagnosis of PFO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TCD has been demonstrated to have high sensitivity and specificity for detection of rightto-left shunting when compared to contrast transesophageal echocardiography and is superior to transthoracic echocardiography. [15][16][17][18][19][20][21][22] Transthoracic echocardiography (TTE) with agitated saline has decreased sensitivity of detecting an intracardiac shunt in OSA patients with elevated BMI and large body habitus secondary to limited acoustic windows. 13,21 Using passage of a guide wire across the atrial septum during cardiac catheterization with intracardiac echocardiography guidance as the standard for diagnosing a PFO, TCD has a 98% sensitivity for making the diagnosis of PFO.…”
Section: Methodsmentioning
confidence: 99%
“…20,23,24 For contrast, a mixture of saline, blood, and air was used, which is reported to be more effective than agitated saline alone. 15 A mixture of 8 cc normal saline combined with 0.5 cc of air and 1 cc of blood was agitated between 2 syringes connected by a 3-way stopcock and injected into the brachial vein; embolic tracks were then counted over the middle cerebral arteries. The degree of RLS was evaluated by TCD at rest and with the Valsalva maneuver at 40 mm Hg, aided by visual feedback with a manometer device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…V-aCS may also be associated with migraine [4, 5], retinal artery occlusion [6] and decompression sickness in divers [7]. Transcranial Doppler ultrasound (TCD) provides a simple, reproducible [8] non-invasive test for v-aCS with sensitivity 68–100% and specificity 70–100% for PFO detection when compared with transoesophageal echocardiography (TOE) [9, 10]. TCD has the added advantage that it is relatively non-invasive and also detects extra-cardiac shunts such as pulmonary arterio-venous malformations [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the ideal time to perform the VM is five seconds after contrast agent (CA) infusion, but these studies were done preferentially with agitated saline solution (AS) or a galactose-based CA 1,3,4 . Studies used a small sample of a patient's own blood to obtain an agitated saline solution with blood (ASb) as a means of increasing the number of microbubbles (MBs) generated compared to AS 5 . The aim of this study was to compare two different timings of the VM with the infusion of ASb as a CA.…”
mentioning
confidence: 99%